(untitled) (Annals of Medical Research, 2026)
Aim: The literature highlights the overlap between Attention-Deficit/Hyperactivity Disorder (ADHD) and Autism Spectrum Disorder (ASD), yet the impact of subclinical autistic traits on feeding behavior in ADHD populations remains underexplored. This study aims to investigate eating behaviors in children diagnosed with ADHD compared with those of typically developing peers, and to assess how elevated autistic traits influence eating behaviors within the ADHD group. Materials and Methods: A cross-sectional comparative design was employed, involving 67 children with ADHD and 75 healthy controls. Data were collected using the Children’s Eating Behavior Questionnaire (CEBQ) and the Social Responsiveness Scale (SRS). Within the ADHD group, participants were stratified by the presence of autistic traits. Group comparisons and correlational analyses were conducted to examine associations between autistic traits and feeding behaviors. Results: Compared with controls, children with ADHD exhibited significantly higher Desire to Drink scores and lower Emotional Under-Eating scores. Within the ADHD group, those with autistic traits had significantly higher Food Fussiness scores than those without autistic traits. Correlation analyses revealed significant associations between total SRS scores and multiple CEBQ subscales, including Emotional Overeating, Desire to Drink, Satiety Responsiveness, and Food Fussiness. Subscales, such as Pathognomonic Autistic Behaviors and Reciprocal Social Behavior, were especially predictive of disordered eating patterns. Conclusion: Findings suggest that autistic traits—even at subclinical levels—are significantly associated with maladaptive eating behaviors in children with ADHD. These results emphasize the importance of transdiagnostic approaches in clinical assessments, moving beyond categorical diagnoses. Understanding the dimensional interplay between ADHD symptoms and autistic traits may improve early nutritional interventions and individualized treatment strategies.